2008
DOI: 10.1080/01496390701748752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flocculation on Critical Flux during Crossflow Microfiltration of Bentonite Suspensions

Abstract: The effectiveness of polymeric flocculant addition and hydrodynamics on increasing the critical permeation flux, J crit , during crossflow microfiltration of bentonite suspensions using a tubular ceramic membrane module was investigated. The investigation determined the effects of flocculant concentration on J crit at various crossflow velocities. The best filtration performance (highest J crit ) was obtained at a flocculant dose of 500 mg kg -1 (mg of flocculant per kg of solids) and at a crossflow velocity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The reduced benefit is likely due to selective deposition of smaller particles because of greater shear-induced back diffusion of larger particles [18,21,[23][24][25].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The reduced benefit is likely due to selective deposition of smaller particles because of greater shear-induced back diffusion of larger particles [18,21,[23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…Flocculation has found extensive use in the waste water and biotechnology industries to aid in separation techniques, such as filtration, flotation, sedimentation [16], and centrifugation [17], where rate improves with the size of the suspended particles. Previous studies have shown that the addition of a polyelectrolyte flocculant results in increased permeate flux rates for the crossflow microfiltration of yeast cells [18,19], CHO cell suspensions [20] in simple media, bentonite [21], and titanium oxide in deionized water [22], but microfiltration of a complex media broth has not been examined.…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies employ the critical flux, rather than steady-state flux, as a reference flux for the study of filtration parameters (such as crossflow velocity, slurry particle size, or eletrokinetic effects). Examples include Chellappah et al (2008), Chong et al (2008), Kim and Zydney (2006), and Huisman et al (1999b). As stated above, critical flux is related to conditions that lead to the incipient deposition of particles on the filter surface.…”
Section: 7mentioning
confidence: 99%
“…Mixing conditions also impacted the degree of flocculation (and permeate flux improvement). Chellappah et al (2008) presented another flocculation study. This study examined the increase in critical flux (i.e., the flux below which no fouling occurs) observed in crossflow microfiltration of bentonite suspensions upon addition of flocculent.…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation